A Study on Teaching English through Literature: Teachers’ Knowledge, Attitudes and Classroom Practices - Almuhairi, Amena Ghanem Adhed Ghanem (2013)
This study is an attempt to investigate teaching English language through literature, which is of increasing importance in the context of learning English as a second language. In the United Arab Emirates, teaching English in government secondary schools mainly aims at preparing students for Higher Education. However, teaching English through literature seems not to be given a priority. To explore its importance, the study reviews the relationship between English language and literature and reports the findings of studies on English language teachers’ knowledge, attitudes and practices for teaching English through literature in a number of countries. This study, therefore, attempts to examine teachers’ literary knowledge, attitudes and classroom practices in regard to this teaching strategy at a government secondary school in Dubai. A qualitative research design was employed to collect data through semi-structured interviews. The sample consisted of three female English language teachers and they constituted the case studies of this research project. The results show that teaching literary texts is an optional activity and marginalised because of the concentration on teaching English language skills, which students struggle to master. The study also reveals that teachers possess knowledge of literature and positive attitudes towards teaching English through literature. They use the communicative approach, student-centered techniques and technological tools in teaching literary texts. Nevertheless, the syllabus, work load and students’ low language level restrict them from employing this teaching strategy. Among the implications of this study, it is necessary to teach both English language and literature to ESL learners by integrating literature into the English language curriculum in the same way as the Arabic language curriculum in the UAE government schools. It also emphasises that literature is a rich resource for enhancing second language acquisition and developing learners’ critical thinking skills, which are required for Higher Education.